Direct costs of osteoporosis and hip fracture: an analysis for the Mexican Social Insurance Health Care System Costos directos de la osteoporosis y fracturas de cadera: un análisis para el sistema de salud mexicano - Fernando Carlos; Patricia Clark; Humberto Maciel; Juan A Tamayo (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: To compare costs of diagnosis and annual treatment of osteoporosis and hip fracture between the Instituto Nacional de Rehabilitación (INR) and the protocol used by the Seguro Popular de Salud (SPSS). METHODS: Direct costs gathered in a prospective study with real cases at the INR are presented, and then this data is re-analyzed with the methodology and protocol for the SPSS to estimate the costs of those cases if treated with the SPSS protocol. RESULTS: Important differences were found in the cost of hip fracture: the SPSS estimates ($37 363.73 MXN) almost double the INR cost ($20 286.86 MXN ). This discrepancy was caused by the different types of surgeries the INR and SPSS protocols call for (the SPSS assumes that all hip fractures will necessitate a hip replacement) and the cost of subsequent hospitalization. A prospective study at the SPSS is needed to validate these results. CONCLUSIONS: Important differences were found between treatment of the same osteoporosis related problems at the INR and SPSS. We recommend revising the SPSS protocol to include less costly surgical treatments. OBJETIVO: Realizar una comparación de costos de diagnóstico y tratamiento anual de la osteoporosis y la fractura de cadera entre el Instituto Nacional de Rehabilitación (INR) y el protocolo utilizado por el Seguro Popular de Salud (SPSS). MATERIAL Y MÉTODOS: Los costos directos obtenidos en un estudio prospectivo con casos reales en el INR fueron utilizados para realizar un escenario considerando la metodología y protocolo del SPSS para estimar los costos de este último. RESULTADOS: Existen diferencias importantes en el costo de la fractura de cadera utilizando el escenario de SPSS; los costos estimados en SPSS fueron casi del doble respecto al INR ($37 363.73 vs. $20 286.86 pesos). Las diferencias están dadas por el tipo y costo de la cirugía (el SPSS asume que todas las fracturas de cadera tengan un remplazo total de cadera) y el costo de la hospitalización. Se requiere un estudio prospectivo para validar estos resultados en el SPSS. CONCLUSIONES: Se encontraron diferencias importantes entre el tratamiento de problemas relacionados con osteoporosis en el INR y el SPSS. Se recomienda revisar el protocolo del SPSS para incluir tratamientos quirúrgicos menos costosos.